Effect of an educational curriculum according to the strategy of mental maps on kinetic abilities and offensive game plans in football in university students - Obaid Aziz, Adnan Khairi; Radi Aljnabi, Ahmed Hatem; Abdul Ameer, Bahaa Hussein (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this paper was to identify the effect of an educational curriculum according to the strategy of mental maps on kinetic abilities and offensive game plans in football in university students. The present study had an experimental design. The present study was conducted on the students of the fourth stage of the College of Physical Education and Sports Sciences at the University of Babylon for the academic year 2020-2021, within the time frame of October 2021 to January 2022. The study was conducted in the stadium of the Faculty of Physical Education and Sports Sciences at the University of Kufa. A total of 40 students were recruited as the participants of the study. Participants were allocated into two groups, experimental group and control group, by simple random allocation method (raffle) with n=20 in each group. Based on the findings of the study, the researchers concluded that the educational curriculum, according to the mental maps strategy, significantly contributed to the development of the kinetic abilities under discussion.